Behavioural economics narratives as a tool for antitrust regulation and ensuring competitiveness under martial law - Zakharova, Kseniia; Захарова, Ксенія Федорівна (Університет «КРОК», 2026)
Global geopolitical shifts and martial law fundamentally alter the functioning conditions of the Ukrainian economy, demanding an immediate transformation of approaches to competition protection. Traditional antitrust regulation methods that rely solely on structural market parameters demonstrate limited effectiveness in crisis realities. Market entities increasingly exploit consumer cognitive vulnerabilities to reinforce their market power. In times of crisis, behavioral aspects of market relations acquire special significance, as information asymmetry directly affects decision-making by economic agents. Therefore, the study of integrating behavioral economics tools into the national antitrust regulation system becomes highly relevant for ensuring economic stability. This scientific work aims to provide a theoretical substantiation and develop practical recommendations on applying behavioral narratives as a cutting-edge antitrust policy tool. The process of antitrust regulation of market structures and ensuring the competitive advantages of enterprises under crisis conditions serves as the object of this study. To achieve the set goal, the author applies the comparative analysis method, economic-statistical modeling, and secondary data analysis. The research results clearly demonstrate that in a crisis economy, market power operates through a purposeful influence on choice architecture, cognitive biases, behavioral inertia, price framing, and algorithmic ranking of information. The author proves that using default settings, anchoring effects, and recommendation systems creates hidden barriers to market entry. Empirical analysis reveals that the application of manipulative price framing increases the probability of a consumer choosing a dominant seller's product by 34,5%. The implementation of algorithmic recommendations provides dominant players with a 22% increase in audience loyalty, which restricts small business development. Modeling shows that 68% of consumers make economic decisions under the influence of wartime anxiety narratives, which unfair market participants exploit to improperly increase prices by an average of 15,4-18,2%. At the same time, for Ukrainian exporters, narratives of resilience and reliability become an important intangible asset that increases the volume of foreign contracts by 12,8%. Integrating behavioral economics into antitrust regulation shifts the focus from a formal analysis of market structure to the protection of genuine freedom of consumer choice. The practical significance of the obtained results lies in the possibility of their direct use by the Antimonopoly Committee of Ukraine to modernize the regulatory framework and implement behavioral tests. The recommendations proposed by the author to counter digital manipulations will reduce the level of crisis-driven opportunism in consumer markets by 25% and ensure the maintenance of the state's price stability.
Наративи поведінкової економіки як інструмент антимонопольного регулювання та конкурентоспроможності в умовах воєнного стану
Keywords: behavioral economics; antitrust regulation; competition; monopoly dominant position; choice architecture; defaults; digital markets; international competitiveness; martial law; sustainable development; postwar reconstruction